Mixing in the process industries - Harnby, N.; Edwards, M. F.; Nienow, A. W. (Butterworth-Heinemann, 1997)
This volume is a valuable reference work for the student and the practising engineer in the chemical, pharmaceutical, minerals, food, plastics, paper and metallurgical industries. The second edition of this successful text has been thoroughly rewritten and updated. Based on the long running post-experience course produced by the University of Bradford, in association with the Institution of Chemical Engineers, it covers all aspects of mixing, from fundamentals through to design procedures in single and multi-phase systems. Experts from both industry and academia have contributed to this work g.
Keywords: Mixing.; elektronické knihy; electronic books